Single-Cell Co-expression Analysis Reveals Distinct Functional Modules, Co-regulation Mechanisms and Clinical Outcomes - Wang, Jie; Xia, Shuli; Arand, Brian; Zhu, Heng; Machiraju, Raghu; Huang, Kun; Ji, Hongkai; Qian, Jiang (PLOS Computational Biology, 2016)
Author Summary With the development of single-cell sequencing, an increasing number of biological insights were revealed at the single-cell resolution. Here we integrated the expression profiles from single cells and bulk tissues to discover that a majority of gene pairs were specifically co-expressed at single-cell and bulk levels. Our comparative analysis reveals co-expressed functional modules at different levels, and suggests a distinct regulatory mechanism in which single-cell co-expressed genes are regulated through physical interactions from different chromosomes. Moreover, we found a set of co-expressed genes to predict patient survival. This study suggests that single-cell and bulk co-expression analysis could provide novel biological insights and great clinical potential.